Hominin presence in Eurasia by at least 1.95 million years ago - Sabrina C. Curran; Virgil Drăgușin; Briana Pobiner; Michael Pante; John Hellstrom; Jon Woodhead; Roman Croitor; Adrian Doboș; Samantha E. Gogol; Vasile Ersek; Trevor L. Keevil; Alexandru Petculescu; et al. (Nature Communications)
Abstract The timing of the initial dispersal of hominins into Eurasia is unclear. Current evidence indicates hominins were present at Dmanisi, Georgia by 1.8 million years ago (Ma), but other ephemeral traces of hominins across Eurasia predate Dmanisi. However, no hominin remains have been definitively described from Europe until ~1.4 Ma. Here we present evidence of hominin activity at the site of Grăunceanu, Romania in the form of multiple cut-marked bones. Biostratigraphic and high-resolution U-Pb age estimates suggest Grăunceanu is > 1.95 Ma, making this site one of the best-dated early hominin localities in Europe. Environmental reconstructions based on isotopic analyzes of horse dentition suggest Grăunceanu would have been relatively temperate and seasonal, demonstrating a wide habitat tolerance in even the earliest hominins in Eurasia. Our results, presented along with multiple other lines of evidence, point to a widespread, though perhaps intermittent, presence of hominins across Eurasia by at least 2.0 Ma.